SIMULATION OF SOME OIL SPILL SCENARIOS IN CON CO ISLAND AREA - Tu, Tran Anh; Cuong, Le Duc (Vietnam Journal of Marine Science and Technology, 2014)
The Con Co Island plays an important role in the economic and security development strategy of Vietnam. The need for petroleum consume is more increasing in the world leading to the increase of petroleum transportation. Located near the petroleum transport line from Middle East to North East Asia, Con Co Island will be affected if oil spills happen. By using Delft3D model and nesting technique, some scenarios of oil spill (100 tons) in different wind directions in Con Co area are simulated. Calculating results show that, with the North-East wind case, the oil slick spreads in 9-14 days; in the case of southern wind, oil slick spreads in 6-9 days and the case of South Wets, oil slick spread in 12-14 days. The results are reference for marine management agencies and related sectors.